Towards sustainable adaptation: A tool for estimating adaptation costs to climate change for smallholder farmers - Shoko Kori, Dumisani; Kori, Edmore (Frontiers in Climate, 2022)
Adaptation reduces the harmful effects of climate change. Nonetheless, the process of adaptation is associated with costs. If these costs are not managed accordingly, they have the potential to deter adaptation thereby impacting on its sustainability. Estimating adaptation costs to climate change provides vital information for decision-making among resource constrained smallholder maize farmers and enhances sustainable adaptation. However, there is no method for estimating adaptation costs that caters for the needs of smallholder maize farmers. Therefore, it was imperative to develop a context-specific tool for estimating adaptation costs for smallholder maize farmers using a bottom-up approach. Principles of quantification of theoretical constructs including conceptualization, operationalisation and attribute development were adopted in developing the tool for estimating adaptation costs to climate change. The tool is composed of three evaluation tools and three adaptation costs equations for the pre-, during- and post-adaptation phases, a total adaptation costs equation and a Summated Rating Scale for sustainability of adaptation activities. The tool is user-friendly, relatively easy to use, can be interpreted easily and modified to suit different smallholder farmers. It is hoped that the tool will assist smallholder maize farmers to consider all factors of critical importance before implementing adaptation plans and ensure reduced adaptation costs while enhancing sustainability.